B-lines Visualization and Lung Aeration Assessment: Mind the Ultrasound Machine Setting. (March 2019) - Mongodi, Silvia; Stella, Andrea; Orlando, Anita; Mojoli, Francesco
Abstract : Supplemental Digital Content is available in the text.